Maladministration on Mining Business Licenses: Case Study “Mining Business License Production Operation PT. Aneka Tambang, Tbk.” - Ahmad Rustan; Ju Lan Hsieh; Wahyudi Umar (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
As a potential natural wealth, mining sectors should be managed with proper rules. Therefore, control instruments are needed in the form of mining business licenses to prevent the negative impact of mining management. At the stage of production operations, the requirements that must be met by businesses are administrative, technical, environmental, and financial. This paper aims to describe maladministration in the issuance of mining business license process especially on upgrading process of exploration permits to production operating permits. This research is a normative juridical research with statute approach and case approach. The results showed that the issuance of mining business license production operation (IUP OP) of PT. Aneka Tambang, Tbk based on the Decree of the Regent of North Konawe No. 158 of 2010 does not meet the technical requirements, especially regionally because the IUP is overlapping 11 other IUP with the same commodity, and there is an IUP OP area which not a part of the exploration area.